Hysteresis in the Third Space? Pupils’ and Their Parents’ Fitting Process to the Hidden Curriculum of New Literacy Practices (Journal of Education and Development, 2018)
New literacies offer new spaces for literacy learning and teaching in schools and influence the social structures of the classroom community through the pupils’ possibilities for collaboration and communication. The social structures in education are often referred with the concept of hidden curriculum, because the social equities/inequities are indicated in hidden messages, for example in values, attitudes and beliefs. This study explored the hidden literacy curriculum in a Finnish first-grade classroom community experiencing a change of traditional literacy practices towards new literacies. We chose Bourdieu and Gee as our thinking companions because their theoretical concepts involving change and identity building enabled us to gain a better understanding of the phenomena. We followed the pupils’ and the parents’ ways of fitting to the change. It became evident that the teachers need to support the pupils as well as the parents and to use different tactics for making the change successful.